The Meaning of Work among Elderly Informal Workers in Sekotong, Indonesia - Maya Atri Komalasari; Moh Taqiuddin; Azhari Evendi; Aliya Rahmawati; Ikrima Fina Hayati (Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The elderly experience a dual vulnerability as both older adults and informal workers; nonetheless, they continue to choose to work. This study aims to uncover the meaning behind the decision to work among elderly informal workers in Sekotong, West Nusa Tenggara. The research is examined utilizing Schutz’s motive theory and the concept of role. Employing a qualitative phenomenological method, data were collected through in-depth interviews, observation, and documentation. Informants were selected purposively, and data analysis was conducted using phenomenological techniques. The results indicate that the meaning behind the elderly’s decision to work is shaped by their perspectives on the aspects of working, alongside the concepts of the "because-motive" and the "in-order-to-motive." Two distinct meanings of work emerge among these elderly informal workers. First, working is viewed as "obligatory" to fulfill daily necessities and maintain social self-esteem. This meaning is constructed by elderly breadwinners who live alone and those who serve as heads of households. Second, working is perceived as "non-obligatory," voluntary in nature, and non-determinant of self-esteem. This second meaning is constructed by elderly dependents who do not serve as heads of households.